The Epistemology by John Duns Scotus (Damascus University Journal of arts and humanities sciences, 2023)
Doubt in the ability of the mind to acquire a certain knowledge diminishes its value and reduces it, and makes the knowledge which it perceives unreliable and lacks the criterion that guarantees its validity. The epistemology of John Duns Scotts shows through his criticism of the theory of illumination and the clarification of certain types of knowledge that the mind is capable of obtaining fixed knowledge by relying on its natural capabilities without the need for divine illumination, where sensory experience plays an important role in the formation of fixed general concepts that form the basis on which the certain knowledge is based. The mind - by relying on sensory perception - is able to form a fixed cognitive structure based on the world of sensory existent, which has been transformed into intelligible entities and images that form the basis for making judgments.
Keywords: Epistemology; Criticism of Illumination; John Duns Scotus